Integrated nonlinear optical imaging microscope for on‐axis crystal detection and centering at a synchrotron beamline. (3rd May 2013) - Madden, Jeremy T.; Toth, Scott J.; Dettmar, Christopher M.; Newman, Justin A.; Oglesbee, Robert A.; Hedderich, Hartmut G.; Everly, R. Michael; Becker, Michael; Ronau, Judith A.; Buchanan, Susan K.; Cherezov, Vadim; Morrow, Marie E.; et al.
<x xml:space="preserve">Abstract</x> Nonlinear optical (NLO) instrumentation has been integrated with synchrotron X‐ray diffraction (XRD) for combined single‐platform analysis, initially targeting applications for automated crystal centering. Second‐harmonic‐generation microscopy and two‐photon‐excited ultraviolet fluorescence microscopy were evaluated for crystal detection and assessed by X‐ray raster scanning. Two optical designs were constructed and characterized; one positioned downstream of the sample and one integrated into the upstream optical path of the diffractometer. Both instruments enabled protein crystal identification with integration times between 80 and 150 µs per pixel, representing a ∼103–104‐fold reduction in the per‐pixel exposure time relative to X‐ray raster scanning. Quantitative centering and analysis of phenylalanine hydroxylase from Chromobacterium violaceum cPAH, Trichinella spiralis deubiquitinating enzyme TsUCH37, human κ‐opioid receptor complex kOR‐T4L produced in lipidic cubic phase (LCP), intimin prepared in LCP, and α‐cellulose samples were performed by collecting multiple NLO images. The crystalline samples were characterized by single‐crystal diffraction patterns, while α‐cellulose was characterized by fiber diffraction. Good agreement was observed between the sample positions identified by NLO and XRD raster measurements for all samples studied.